Assessing and predicting the value of ecosystem services in Sanya City, Hainan Island, China - Peihong Song; Qiu Yang; Wenyin Wu; Tianyan Su; Yamin Jiang; Jingli Lu; Zhongyi Sun; Jie Zhang; Rui Yu; Peng Wang; Lan Wu; Huai Yang; et al. (Ecological Indicators)
Recognizing and assessing the value of ecosystem services (ESV) is crucial for ecosystem management, conservation, and the promotion of sustainable development. Land use/cover change (LUCC) plays an important role in evaluating regional ESV. In this study, the ESV of Sanya City in 2000, 2010, and 2020 was evaluated using the equivalent coefficient method. Additionally, the Future land-use simulation (FLUS) model was employed to predict land-use changes in 2030 under five different scenarios. Factors influencing ESV and their interactions were analysed using convergent cross mapping (CCM) and global sensitivity and uncertainty analysis (GSUA). The results indicated that, from 2000 to 2020, forest, cultivated land and unutilized land areas decreased by 61.28 km2, 46.32 km2, and 1.91 km2, respectively, while water areas increased by 8.29 km2 and construction land expanded by 102.53 km2. Overall, ESV showed a fluctuating but overall declining trend, with values of 75.59 × 108 yuan in 2000, 78.23 × 108 yuan in 2010, and 74.59 × 108 yuan in 2020. High ESV were predominantly found in inland areas, while low values were prevalent in the coastal built-up areas. Based on Ecological Protection and Synthetical Protection Scenarios, ESVs in 2030 were projected to increase by 2.78 × 108 yuan and 2.26 × 108 yuan, respectively, when compared to the Natural Development Scenario, due to the restricted conversion of cultivated land and forest into construction land. This study found that Gross Domestic Product (GDP), Normalized Difference Vegetation Index (NDVI), and population had significant impacts on ESV, while forest and water areas exhibited notable individual impact. Considering the LUCC characteristics and land-use strategies in Sanya, the Synthetical Protection Scenario was identified as the optimal choice to balance the red line between farmland and the ecological development of civilization. This study recommends the reasonable planning of urban construction land, the expansion of urban green space, and the strengthening of ecological land conservation. These findings offer valuable theoretical insights for the sustainable development of Sanya City.